Momordica charantia L. Fruit Fractions inhibit Malondialdehyde Level and Regenerate Hepatic Damage of Hyperglycemic Rats - Parawansah Parawansah; I Putu Sudayasa; Andi Noor Kholidha Syarifin; Amirudin Eso; Nuralifah Nuralifah; Wa Ode Siti Rahayu Fathanah; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Chronic hyperglycemia causes an increase of free radical production and in longterm, the hyperglycemia increases oxidative stress. Among medicinal plants, Momordica charantia L. fruit has been known to overcome hyperglycemia. However, role of M. charantia L. fruit on oxidative stress is not well understood. Therefore, current study was conducted to investigate the effect of M. charantia L. fruit extract on malondialdehyde (MDA) level and hepatic damage in hyperglicemic rat model.METHODS: Twenty five white rats (Rattus novergicus) were induced with Streptozotocin (STZ) and treated with/without glibenclamide, sodium carboxymethyl cellulose (Na-CMC), or M. charantia L. fruit ethanol/ethyl acetate/ n-hexane fraction. After the treatment, rat’s livers were collected and separated for histopathological examination and MDA analysis.RESULTS: The MDA level average of rats before the STZ induction was 1.37 μg/mL. MDA level average was markedly increased (23.85 μg/mL) in rats induced with STZ and treated with Na-CMC merely. The MDA level average of STZ-induced glibenclamide-treated rats was 3.12 μg/mL. Meanwhile, the MDA level averages of STZ-induced M. charantia L. fruit ethanol, ethyl acetate and n-hexane fractions-treated rats were 14.95, 8.98 and 5.37 μg/mL, respectively. The histopathology results of this study showed that adipocytes, dilated sinusoids and central vein thickening were mostly observed in STZ-induced Na-CMC-treated rats. Meanwhile, the STZ-induced ethanol/ethyl acetate/n-hexane fraction-treated rats did not exhibitthose expressions.CONCLUSION: M. charantia L. fruit fractions inhibit the MDA level average in liver tissue and regenerate hepatic damage of STZ-induced rats, especially the n-hexane fraction which could be a potential hepatic antioxidant and regenerative agent.KEYWORDS: Momordica charantia L., malondialdehyde, oxidative stress, hyperglycemia, diabetes mellitus